Sacral arachnoid cyst presenting as chronic low back pain (Bangladesh Journal of Medical Science, 2014)
DOI: http://dx.doi.org/10.3329/bjms.v14i1.16191 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.106-108